Abundant glutamic acid decarboxylase (GAD)‐reactive B cells in gad‐antibody–associated neurological disorders. Issue 3 (28th January 2019) - Thaler, Franziska S.; Thaller, Anna L.; Biljecki, Michelle; Schuh, Elisabeth; Winklmeier, Stephan; Mahler, Christoph F.; Gerhards, Ramona; Völk, Stefanie; Schnorfeil, Frauke; Subklewe, Marion; Hohlfeld, Reinhard; Kümpfel, Tania; et al.
Abstract : High levels of antibodies against glutamic acid decarboxylase (GAD) are observed in patients with different neurological disorders, but cells producing these autoantibodies are largely unexplored. We detect circulating GAD‐reactive B cells in peripheral blood that readily differentiate into antibody‐producing cells. These cells are highly elevated in most patients with GAD‐antibody–associated disorders (n = 15) compared to controls (n = 19). They mainly produce GAD65 antibodies of the IgG1 and IgG4 subclasses and are as abundant as B cells reactive for common recall antigens. Bone marrow cells represent an additional source of GAD antibodies. The identification of GAD‐antibody–producing cells has implications for the selection of cell‐specific biologics. ANN NEUROL 2019;85:448–454.